Correction for QT/RR Hysteresis in the Assessment of Drug‐Induced QTc Changes—Cardiac Safety of Gadobutrol - Malik, Marek (Ann Noninvasive Electrocardiol, 2009)
Background: The so‐called thorough QT/QTc (TQT) studies required for every new pharmaceutical compound are negative if upper single‐sided 95% confidence interval (CI) of placebo and baseline corrected QTc prolongation is <10 ms. This tight requirement has many methodological implications. If the investigated drug has a fast action and ECGs cannot be obtained at stable heart rates, QT/RR hysteresis correction is needed. Methods: This was used in a TQT study of gadobutrol. The TQT study was a randomized double‐blind five‐times crossover study of three doses of gadobutrol (0.1, 0.3, and 0.5 mmol/kg) that was placebo and positive effect controlled (moxifloxacin 400 mg). The study enrolled 50 healthy subjects with data of all periods. QT/RR hysteresis was assessed from prestudy exercise test ECGs. Among others, comparisons were made between population heart rate correction without hysteresis considerations and combined population heart rate and hysteresis correction. Results: The highest heart rate increase (placebo and baseline controlled) of 13.1 beats per minute (90% CI 9.9–16.4) occurred 1 minute after the administration of the highest dose of gadobutrol. Without hysteresis consideration, the highest ΔΔQTc were 9.91 ms (90% CI 8.01–11.81) while with hysteresis correction, these values were 7.62 ms (90% CI 6.37–8.87), thus turning a marginally positive TQT study into a negative finding. Conclusion: Hence, omitting hysteresis correction from episodes of fast heart rate changes may lead to incorrect conclusions. Despite substantial rate acceleration, accurate hysteresis correction confirms that gadobutrol does not have any effects on cardiac repolarization that would be within the limits of regulatory relevance.